Adjusting White OLEDs with Yellow Light Emission Phosphor Dye and Ultrathin NPB Layer Structure - Jun Wang; Weizhi Li (International Journal of Photoenergy)
High efficiency white organic light emission devices were demonstrated with phosphor material dye bis[2-(4-tertbutylphenyl)benzothiazolato-N,C2′]iridium (acetylacetonate) and ultrathin layer structure. The ultra thin layer be composed of 4,4′-bis[N-1-naphthyl-N-phenyl-amino]biphenyl (NPB) or 4,4′-N,N′-dicarbazole-biphenyl : NPB mixed layer with blue light emission. The emission spectra of devices could be adjusted by different phosphor doping concentrations and ultra thin layer structure. Warm white light emitting device could be obtained with 5 wt% doping concentration and power efficiency of 9.93 lm/W at 5 V. Pure white light with Commission Internationale de l'Eclairage (CIE) coordinates of (0.33, 0.30) and external quantum efficiency of 4.49% could be achieved with ultra thin layer device structure and 3 wt% phosphor doped device.